Intellectual Capital sebagai Pemoderasi Pengaruh Loan to Deposit Ratio dan Ukuran Perusahaan terhadap Kinerja Keuangan - Saputra, Agus Krisna; Gayatri, Gayatri (E-Jurnal Akuntansi, 2023)
The study aims to determine the effect of Loan to Deposit Ratio and Company Size on Financial Performance with Intellectual Capital as moderation. Moderating variables are variables that can strengthen or weaken the relationship between the Loan to Deposit Ratio and Corporate Performance Measures on Financial Performance. This research was conducted at banking companies listed on the Indonesia Stock Exchange (IDX). The population in this study were all banking companies listed on the Indonesia Stock Exchange totaling 45 companies. Determination of the sample using purposive sampling method. Banking companies selected as research samples were 32 companies. The analysis technique uses the Moderated Regression Analysis (MRA) method. The results of the analysis show that the Loan to Deposit Ratio (LDR) has no significant effect on financial performance (ROA), firm size (SIZE) has a positive and significant effect on financial performance (ROA), Intellectual Capital moderates the influence of Loan to Deposit Ratio (LDR) and firm size. (SIZE) on Financial performance (ROA) Keywords: LDR; Size; ROA; Intellectual Capital.